Vegetative propagation of Juniperus chinensis - Fragoso, Rosimeri de Oliveira; Zuffellato-Ribas, Katia Christina; Macanhão, Gustavo; Stuepp, Carlos André; Koehler, Henrique Soares (Comunicata Scientiae, 2015)
Juniperus chinensis L. var. kaizuka, belonging to the Cupressaceae family and known as kaizuka is a species widely used in landscaping, being different from the other varieties of the species mainly because of its tortuous growth habits. The sexual reproduction of Juniperus chinensis has disadvantages and its propagation by cuttings can facilitate the production of seedlings. Thus, this study aimed to evaluate the effect of three different concentrations of the synthetic auxin indolebutyric acid (0, 1500 and 3000 mg L-1) to promote rooting of Juniperus chinensis var. kaizuka, collected in the basal (0.5 to 2.0 m), middle (2.1 to 3.5 m) and apical (3.6 to 5.0 m) portions of the stock plant, during winter, spring and autumn of 2012, with the intent to subsidize the development of a propagation protocol for the species. After 140 days in the greenhouse, it was observed that choosing the proper season to collect cuttings is essential for the viability of vegetative propagation technique for Juniperus chinensis var. kaizuka, with the recommendation of spring as the more suitable season for rooting development. However, although the application of AIB and the collection height in the stock plant have shown significant effects on some variables, it wasn’t observed a standard, related to these factors, producing a greater induction of the radicial system of the species.